The association between the severity of chronic kidney disease and medical costs among patients with type 2 diabetes. (4th May 2019) - Lage, Maureen J.; Boye, Kristina S.; Bae, Jay Patrick; Wu, Jianmin; Mody, Reema; Botros, Fady T.
Abstract: Aims: Examine healthcare costs across chronic kidney disease (CKD) stages for US patients with type 2 diabetes (T2D). Materials and methods: IQVIA Real World Data Adjudicated Claims linked electronic medical records and insurance claims from January 1, 2012 through March 31, 2017 were used for this retrospective study. Adults diagnosed with T2D and comorbid CKD were included. General linear models incorporating splines were constructed, and information from these regressions were used to inform the relationship between medical costs and CKD. Multivariable analyses controlled for patient characteristics, vital signs, general health, prior medication use, prior visit to specialists, index A1c, and year of index date. Results: There were 6, 645 individuals who met the study criteria. Results generally indicate sharp increases in annual total medical costs and non-drug medical costs in the 1 year post-period for patients with Stage 4 or 5 CKD (estimated glomerular filtration rate [eGFR] ≤ 30 mL/min/1.73 m 2 ) with each 1 point reduction in eGFR from 30 associated with an increase of 1, 870 in all-cause total medical costs ( p < 0.0001) and 1, 805 of all-cause non-drug medical costs ( p < 0.0001). Similarly, each point decline below 30 mL/min was associated annual cost increases of 1, 701 for CKD-related total medical costs, 1, 695 for CKD-related non-drug medical costs, 173 for diabetes-related medical costs, and 187 for diabetes-related non-drug medical costs (all p < 0.0001). Limitations: The investigation included only patients with medical insurance and laboratory test results, and results may not be generalizable to all T2D patients with CKD. The methodology allowed us to determine associations, not causation, and potential confounders, such as duration of diabetes, diet, exercise, or social support, could not be assessed. Conclusions: Results indicate there are sharp and significant increases in medical costs among T2D patients with Stage 4 and 5 CKD compared to those with earlier stages of CKD.